The role of peptidyl-prolyl isomerase Pin1 in neuronal signaling in epilepsy - Chen, Yuwen; Hou, Xiaojun; Pang, Jiao; Yang, Fan; Li, Angcheng; Lin, Suijin; Lin, Na; Lee, Tae Ho; Liu, Hekun (Frontiers in Molecular Neuroscience, 2022)
Epilepsy is a common symptom of many neurological disorders and can lead to neuronal damage that plays a major role in seizure-related disability. The peptidylprolyl isomerase Pin1 has wide-ranging influences on the occurrence and development of neurological diseases. It has also been suggested that Pin1 acts on epileptic inhibition, and the molecular mechanism has recently been reported. In this review, we primarily focus on research concerning the mechanisms and functions of Pin1 in neurons. In addition, we highlight the significance and potential applications of Pin1 in neuronal diseases, especially epilepsy. We also discuss the molecular mechanisms by which Pin1 controls synapses, ion channels and neuronal signaling pathways to modulate epileptic susceptibility. Since neurotransmitters and some neuronal signaling pathways, such as Notch1 and PI3K/Akt, are vital to the nervous system, the role of Pin1 in epilepsy is discussed in the context of the CaMKII-AMPA receptor axis, PSD-95-NMDA receptor axis, NL2/gephyrin-GABA receptor signaling, and Notch1 and PI3K/Akt pathways. The effect of Pin1 on the progression of epilepsy in animal models is discussed as well. This information will lead to a better understanding of Pin1 signaling pathways in epilepsy and may facilitate development of new therapeutic strategies.